The 12 worst health disasters of all time - Hamen, Susan E. (All-time worst disasters., 2019)
Profiles history's twelve worst health disasters, documenting their location, lives lost, and legacy. Each profile includes images and statistics, and select entries include critical thinking questions. Includes tips on how to stay safe during a health crisis, a glossary, sources for further information, and an index.